Respuesta :

Greetings from Brasil...

According to the statement of the question, we can assemble the following system of equation:

X · Y = - 2      i

X + Y = 7       ii

isolating X from i and replacing in ii:

X · Y = - 2

X = - 2/Y

X + Y = 7

(- 2/Y) + Y = 7     multiplying everything by Y

(- 2Y/Y) + Y·Y = 7·Y

- 2 + Y² = 7X     rearranging everything

Y² - 7X - 2 = 0      2nd degree equation

Δ = b² - 4·a·c

Δ = (- 7)² - 4·1·(- 2)

Δ = 49 + 8

Δ = 57

X = (- b ± √Δ)/2a

X' = (- (- 7) ± √57)/2·1

X' = (7 + √57)/2

X' = (7 - √57)/2

So, the numbers are:

(7 + √57)/2

and

(7 - √57)/2